Influence of multiple islands on the hysteresis and dynamics of a western boundary current perturbed by a mesoscale eddy at a gap - Kunshan Li; Huan Mei; Xiangbai Wu; Jianxin Dong; Qian Liu (Frontiers in Marine Science, 2023)
The hysteresis of a western boundary current (WBC) flowing across a gap and the dynamics of the mesoscale eddy–WBC interaction with the presence of two islands in the gap are studied using a 1.5-layer ocean model. The hysteresis of the WBC suggests that the two islands in the gap facilitate the WBC to intrude into the western basin by shedding eddies compared with the no-island case, but they promote the WBC to leap across the gap compared with the one-island case. The mesoscale eddies from the east of the gap can induce the critical-state WBC shifting from penetration to leap and vice versa. The dynamics revealed by the vorticity balance analysis shows that the increased (decreased) meridional advection of the WBC perturbed by the eddy forces the WBC to leap across (intrude into the western basin through) the gap. We also present the parameter space of the critical strength of the eddy with variable north–south locations inducing the critical WBC transition. For the WBC critical from the eddy-shedding to leaping regime, the regime shift is most sensitive to the anticyclonic eddy from the gap center and to the cyclonic eddy from the southern gap. It is least sensitive to the eddy downstream of the WBC. For the WBC critical from the leaping to eddy-shedding regime, the regime shift is most sensitive to the anticyclonic eddy upstream of the WBC and to the cyclonic eddy from the southern gap. The least sensitive eddy is from the northern gap.